Technical Assistance and Training Services of the International Monetary Fund. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1985)
This paper describes technical assistance and training services of the IMF. The paper highlights that the IMF's responsibility for providing this assistance and its member countries' need to obtain it, arises out of the importance of good economic and financial management and the recognition of the close relationship that exists between domestic financial policies and procedures and balance-of-payments management. The types of assistance provided, typically in the fields of central banking, fiscal matters, and economic and financial statistics, reflect this link.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet